BOXTARIK (BOX PINTAR LISTRIK) INOVASI MEDIA PEMBELAJARAN DENGAN MEMANFAATKAN LIMBAH BOTOL OLI - Toyib Wahyu Nugroho; Nusroh Wulandari; Henry Setya Budhi (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
One of the most important components in the learning process is learning media. Hamlik (1986) suggests that the use of instructional media in the teaching and learning process can increase new desires and interests, increase motivation and stimulation of learning activities, and even bring psychological effects to students. Utilization of used goods and simple equipment as a medium of learning is not something new in the world of education. As is known, waste is a major problem in Indonesia. Based on data from the Central Bureau of Statistics in 2014 shows that Indonesia produces around 187.2 million tons / year of waste and ranks second as the largest waste producer in the world. Waste does not only come from households but also from the automotive environment, for example used oil bottles. Making learning media from used oil bottles aims to arouse creativity and also instill environmental care, so that they will strive to maintain life for the next, besides that it can also grow the entrepreneurial spirit if it can develop its creativity in making learning media. This study uses an experimental method to obtain appropriate learning media and literature studies from several books, journal articles, and other relevant sources.